Policymaking in the open economy : concepts and case studies in economic performance - Dornbusch, Rudiger (New York, N.Y. : Oxford University Press for the World Bank, 1993)
A study which explores how economic policies influence economic performance, this text highlights the areas of monetary policy, exchange-rate policy, financial reform, protection, tax reform and foreign capital.
&#x000A
Includes bibliographical references and index.
oif 31/03/15
Loan
Keywords: Economic policy; Monetary policy; Commercial policy; Fiscal policy; Foreign exchange; Debts, Public